Renal protection by atorvastatin in a murine model of sickle cell nephropathy. (12th March 2018) - Zahr, Rima S.; Chappa, Prasanthi; Yin, Hong; Brown, Lou A.; Ataga, Kenneth I.; Archer, David R.
Summary: Recent studies have demonstrated pleiotropic effects of statins in various mouse models of kidney disease. In this study, Townes humanized sickle cell mice were treated for 8 weeks with atorvastatin at a dose of 10 mg/kg/day starting at 10 weeks of age. Treatment with atorvastatin significantly reduced albuminuria, and improved both urine concentrating ability and glomerular filtration rate. Atorvastatin also decreased markers of kidney injury and endothelial activation, and ameliorated oxidant stress in renal tissues and peripheral macrophages. Atorvastatin downregulated the expression of mRNA levels of the NADPH oxidases, Cybb (also termed Nox2 ) and Nox4, which are major sources of oxidant stress in the kidney. These findings highlight the pleiotropic effects of atorvastatin and suggest that it may provide beneficial effects in sickle cell nephropathy.